Pendidikan anti Korupsi dan Tantangan Internalisasi Moral di Kalangan Mahasiswa Papua - Sandro, Rival Alex; Bao, Bonefasius; Nurak, Anitha (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the implementation of anti-corruption education and the challenges in internalizing the values of honesty, responsibility, and dísciplíne among students at the University of Science and Technology Jayapura (USTJ) Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and document studies involving 50 infomants from five faculties. The findings reveal that although students generally understand the importance of anti-corruption values, their application is hindered by peer pressure, weak role models, and the lack of cultural integration in education. The value of honesty is often conpromised in academic pratices such as cheating and plagiarism: responsibility is shaped by ínteractions with lecturers and family expectations; and discipline is largely understood as mere compliance with rules rather than an internalized ethical commitment. The study enphasizes the need for a contextual, participatory approach rooted in local Papuan culture, including the revitalization of indigenous anti-corruption values such as transparency, accountability, and honesty reflected in the traditional noken philosophy. It recommends integrating character education into curricula, strengthening lecturers exemplary roles, and creating a campus ecosystem that promotes integrity and shame toward dishonest behavior.